Antibacterial property of saline solution on post tooth extraction microflora - Quintos, Michelle Angelica F.
To prevent bacteremia and further incidence of infection associated with tooth extraction, dentists reduce bacterial load in the mouth before, during and after extraction of teeth. Among the post tooth extraction instruction dentists give out is gargling with warm saline solution. The recommended recipe is 1 teaspoon of salt in 8 ounces of warm water, which is a 1.8% saline solution. The aim of the study was to determine if saline solution reduces post tooth extraction bacterial load in an in vitro setting using quantitative analysis. Varying concentrations of saline solutions (0.9%, 1.8%, and 2.7%) were prepared and mixed with dilutions of Streptococcus viridans and Staphylococcus aureus organisms. At contact times 30 and 60 seconds, 10 uL of each mix was spread plated in culture media and incubated for 24 hours at 37 °C. Five replicates were done and 1% Povidone Iodine, an established oral antiseptic, was also used for comparison together with a computed baseline data. Colony count was subjected to the ANOVA and Duncan's Multiple Range Test for statistical analysis. Results showed that no significant decrease in microbial count level is seen between 0.9%, 1.8% and 2.7% saline solution when compared with each other and with the computed baseline data. Significant decrease in colony count is observed for 1% Povidone Iodine when compared with saline solution and baseline data. It may be concluded that in an in vitro setting, saline solution does not inhibit growth of Streptococcus viridans and Staphylococcus aureus and 1% Povidone Iodine significantly inhibited microbial growth and is better than saline solution in this set-up.